ANALISIS TINGKAT KEPUASAN PENGGUNA PADA PENERAPAN SISTEM INFORMASI PENDIDIKAN (DAPODIKMEN) (Studi Kasus: Dindikbudpora Kabupaten Purworejo) - Heri Sudibyo (Politeknik Sawunggalih Aji, 2017)
Analysis of Satisfaction Level Implementation Education Information System (Dapodikmen) Approach Using End User Computing Satisfaction (EUCS), This study aims to determine the level of user satisfaction (user) System informasii education in the region Dindikbudpora Purworejo and as a graduation requirement Strata Two (S2) in MTI STMIK AMIKOM Yogyakarta. That discussion is not wide of the problem studied, the authors restrict this study as follows: Just researching Dapodikmen in Purworejo district, just researching applications or dapodikmen Education Information System and did not examine the network infrastructures and the hardware used. Only use one method penlitian that End User Computing Satisfaction (EUCS). The study was conducted on 43 people as respondent. Collecting data through questionnaires using simple random sampling .. The results showed that the level of user satisfaction at the adoption of Information Systems Education (Dapodikmen) of 5 variables studied, four variables: content, format, easy of use and the timeline stated satisfied. with the average value of each variable as follows, the highest average value is the variable content with a value of 3.39, the 2nd is the easy of use with variable grades 3 to 3.37 which is variable with a value of 3.35 format, the 4th time line is variable with a value of 3.28. and 1 variable is declared not satisfied that the variable accuracy with a value of 3.33. As for how to determine the level of satisfaction by comparing the expected value and the value true, if the expected value is greater than the value of the fact it is declared not satisfied and if the expected value is less than the value true then declared satisfied The level of user satisfaction at the adoption of Information Systems Education or Dapodikmen in the Dindikbudpora Purworejo and measured using user satisfaction (EUCS) at the level to settle for the 4 variables are variables: content, format, easy of use, timeline and 1-level variables are not satisfied that the variable accuracy. Keywords: System, Information, Satisfaction, Variables, User, Levels.